The Relationship between Phosphate Adsorption and Soil Organic Carbon from Organic Matter Addition - Yusran, Fadly Hairannoor (UNIVERSITY OF LAMPUNG, 2010)
The Relationship between Phosphate Adsorption and Soil Organic Carbon from Organic Matter Addition (FH Yusran): The application of organic matter (OM) can increase soil phosphorus (P) availability via soil mineralisation. In lateritic soils, however, soluble organic carbon (OC) from OM may also reduce phosphate adsorption capacity, a process that also releases P in soil solution. In these soils, competitive adsorption could be dominant compared to mineralisation. The main objectives of this study were to study phosphate adsorption in three lateritic soils which have been treated with different types and amounts of organic amendment, and had intrinsic OC removed by combustion. The adsorption isotherms showed that OM addition could reduce phosphate adsorption and that this reduction could last up to nine months after application. Lucerne hay was more effective than peat and wheat straw additions in reducing phosphate adsorption capacity. The bicarbonate phosphorus (BP) release through mineralisation occurred despite the increase of phosphate adsorption capacity due to the combustion of soil samples. Peat treatment was predicted to be more effective in creating organo-metal complexes with Al and Fe. Overall, mineralisation from added organic amendment was effective in minimising P adsorption in lateritic soil.Â